Experimental Research Concerning Relation between Contact Patch and Lapping Operation of Worm Face Gear. (2015) - Gavrilă, Ion; Boloş, Vasile
Abstract: The purpose of this paper is to prove a direct relation between contact patch and lapping, operation which was perform after hobbing and head treatment, for worm face gear compose by a face wheel and a cylindrical worm. The gear's elements were manufacturing from steel and hardened by gas nitride. In the absence of a lapping machine suitable for this gear type, lapping was carried out in specifically stand, using a lapping solution propose by authors. Lapping results are strongly influenced by the initial surface quality in terms material roughness and hardness. By lapping carried out we succeed to increase contact area on both flanks by about 23%. Lapping operation cost is significant but is justified by improving the functioning in charge of the gear with the immediate effect of vibration and noise reduction.